Seasonal profile of trace metal contamination (Hg, Cd, Pb and Al) and biological contamination of atmospheric air in the city of Kinshasa, Democratic Republic of the Congo - Mondo, M. T.; Nsimanda, I. C.; LUSASI SWANA, Willy; Mulaji, K. C.; Pwema, K. V.; Musibono, E. A. D. (Orapuh Journal, 2025)
Introduction Unpleasant fumes, odours, reduced visibility, health issues from pollutants, and property damage caused by dust and corrosive gases are significant challenges in urban and industrial areas. Excessive pollution poses severe risks to health, rendering some areas uninhabitable and hindering socio-economic development. Objective This study aimed to assess the atmospheric air quality in Kinshasa, Democratic Republic of the Congo, by analysing chemical and biological pollution in dust collected at high-traffic intersections. Methods Sampling was conducted over 12 months in 2022, aligned with seasonal variations. Rainwater samples were collected in 500 ml plastic jars placed 5 m above ground, while dust samples were gathered from pre-selected rooftops. The concentrations of chemical pollutants in rainwater and dust were determined using molecular absorption spectrophotometry. Biological pollution was assessed by measuring organic matter in dust and cultivating diaspores from dust samples, with plant species identified using the APG III botanical classification. Results Chemical contamination of rainwater was observed with trace metals varying by site (e.g., Victoire: Hg = 0.43±0.03 mg/kg; Matadi Kibala: Hg = 0.07±0.04 mg/kg). Dust was also contaminated with trace metals (e.g., Victoire: Hg = 5.33±4 mg/kg; Kingasani: Hg = 5.33±4 mg/kg). Additionally, dust contained diaspores from 27 plant species across 16 botanical families, with higher concentrations during the dry season. Conclusion This study revealed poorer air quality in high-traffic areas in downtown Kinshasa compared to less urbanised sites like Mongata and Mbankana. Inhalation of dust and consumption of rainwater in these areas, especially during the dry season, pose health hazards, exposing residents to various diseases. Protective measures, such as mask-wearing, are crucial to safeguarding public health in areas with poor air quality.